Der Bauforscher Arnold Tschira (1910 - 1969) : Gedenkschrift seiner Schüler zum 100. Geburtstag - Böker, Johann Josef [Hrsg.]Ohr, Karlfriedrich [Hrsg.] (Materialien zu Bauforschung und Baugeschichte / Karlsruher Institut für Technologie, Institut Kunst- und Baugeschichte, Fachgebiet Baugeschichte, 2017)
After World War II, the architectural historian Arnold Tschira taught for almost two decades architecture students to understand their future field of activity as a historically shaped environment. His interdisciplinary lectures were attended by students from other faculties as well as an interested audience from outside the university. As a member of the supervisory board of the German Archaeological Institute (Deutsches Archäologisches Institut, DAI) representing his profession, he succeeded Robert Koldewey and Armin von Gerkan and significantly contributed to the field of architectural history research. As the Director of the Institute of Architectural History at the Faculty of Architecture of the University of Karlsruhe (TH), his research activities included, besides the era of antiquity, the architectural art of the Middle Ages in Baden and the classicism of Friedrich Weinbrenner, who founded the first building school in Baden in 1800, from which later the Technical University of Karlsruhe and finally today's research and education institution KIT (Karlsruhe Institute of Technology) were to emerge. This commemorative volume for Arnold Tschira, with which former students and colleagues of his institute trace his career and his fields of activity, represents a piece of research history rooted in the formidable tradition in the field of architectural history in Karlsruhe.